Kedudukan Serikat Pekerja Dalam Penyelesaian Perselisihan Hubungan Industrial Di Denpasar - I Made Gede Bagus Somayasa; Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2025)
Industrialization has led to a decline in workers' autonomy, making them increasingly dependent on their employers. As a result, employers may unknowingly mistreat their workers, citing market competition as justification for their actions. The Decree of the Minister of Manpower of the Republic of Indonesia allows trade unions to be formed based on different criteria such as field of business or type of work. The guideline states that a trade union is an organization that gathers workers of a company and has a management structure at various levels. The problem formulations raised are (1) What is the position of labor unions in the implementation of industrial relations dispute settlement? and (2) How are the implementation obstacles in the settlement of industrial relations disputes? The research method used in this research is the empirical law method. The results show that trade unions play an important role in resolving conflicts in the workplace and protecting workers' rights. The imbalance of power between labor unions and employers internally, as well as resistance or lack of support from management externally, are the main obstacles to resolving industrial relations disputes, causing tension between the two parties.